Ultracold three-body collisions near narrow Feshbach resonances - Wang, Yujun; D’Incao, J. P.; Esry, B. D. (My University, 2011)
We study ultracold three-body collisions of bosons and fermions when the interatomic interaction is tuned near a narrow Feshbach resonance. We show that the width of the resonance has a substantial impact on the collisional properties of ultracold gases in the strongly interacting regime. From our numerical and analytical analyses, we identify universal features dependent on the resonance width. Remarkably, we find that all inelastic processes near narrow resonances leading to deeply bound states in bosonic systems are suppressed, while those for fermionic systems are enhanced. As a result, narrow resonances present a scenario that is the reverse of that found for broad resonances, opening up the possibility of creating stable samples of ultracold bosonic gases with large scattering lengths.